MODEL KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU - Firdaus, Agung; Taqwatul Ulyah; Riskun Iqbal (UNISAN JURNAL, 2023)
the aims of this research are; (1) To explain the leadership model of the Principal of QTA An-Nur Middle School in improving the pedagogic competence of Islamic Religious Education teachers, (2) To describe what strategies were carried out by the Principal of Dwi Mulya Middle School in increasing the pedagogical competence of Religious Education Teachers, and (3) To determine the impact of the strategy the leadership of the Principal on increasing the Pedagogic Competence of Islamic Religious Education Subject teachers at Principal of QTA An-Nur Middle School. This study uses a qualitative approach, with a case study type, with a single case design. Collecting data by interview, observation, and documentation techniques. Data analysis techniques use descriptive analysis with interactive analysis models. To check the validity of the data is done by data triangulation. The results showed that: (1) The Leadership Model of the QTA An-Nur Middle School Principal in Improving the Pedagogic Competence of Islamic Religious Education Subject Teachers that was applied was more oriented towards situational leadership patterns (2) The Principal's Strategy in Improving the Pedagogic Competence of Islamic Religious Education Subject Teachers was by using: a) Ability to manage class, b) Ability in the teaching system, and c) Ability in structuring the classroom climate. (3) The impact of the Principal's Leadership Strategy on Increasing the Pedagogic Competence of Islamic Religious Education Subject Teachers at Dwi Mulya Middle School is the impact of the three strategies, including: teacher competency becomes better, more proactive, teachers are more disciplined, administrative, work ethic increases, more obedient about regulations, effectively preparing tools, student achievement increases, and teachers are more enthusiastic about up-to-date IT-based learning strategies